ABCB1 in children's brain tumours. (9th October 2015) - Coyle, Beth; Kessler, Maya; Sabnis, Durgagauri H.; Kerr, Ian D.
Abstract : Tumours of the central nervous system are the most common solid tumour, accounting for a quarter of the 1500 cases of childhood cancer diagnosed each year in the U.K. They are the most common cause of cancer-related death in children. Treatment consists of surgery followed by adjuvant chemotherapy and/or radiotherapy. Survival rates have generally increased, but many survivors suffer from radiotherapy-related neurocognitive and endocrine side effects as well as an increased risk of secondary cancer. Adjuvant chemotherapy is normally given in combination to circumvent chemoresistance, but several studies have demonstrated it to be ineffective in the absence of radiotherapy. The identification of children with drug-resistant disease at the outset could allow stratification of those that are potentially curable by chemotherapy alone. Ultimately, however, what is required is a means to overcome this drug resistance and restore the effectiveness of chemotherapy. Medulloblastomas and ependymomas account for over 30% of paediatric brain tumours. Advances in neurosurgery, adjuvant radiotherapy and chemotherapy have led to improvements in 5-year overall survival rates. There remain, however, significant numbers of medulloblastoma patients that have intrinsically drug-resistant tumours and/or present with disseminated disease. Local relapse in ependymoma is also common and has an extremely poor prognosis with only 25% of children surviving first relapse. Each of these is consistent with the acquisition of drug and radiotherapy resistance. Since the majority of chemotherapy drugs currently used to treat these patients are transport substrates for ATP-binding cassette sub-family B member 1 (ABCB1) we will address the hypothesis that ABCB1 expression underlies this drug resistance.